Midlife cognitive activity moderates the relationship between brain tau deposition and late‐life cognitive decline - Ko, Kang; Yi, Dahyun; Byun, Min Soo; Lee, Jun Ho; Kim, Yu Kyeong; Lee, Yun‐Sang; Lee, Dong Young (Alzheimer's & dementia, 2020)
Background Cognitive activity (CA), an important modifiable lifestyle factor, has been related to decreased risk of Alzheimer’s disease (AD) dementia, and reduced cerebral beta‐amyloid deposition and neurodegeneration. The relationship between CA and in vivo tau deposition in brain, however, remains still elusive. Hence, we first aim to examine the direct association of CA, midlife CA in particular, with brain tau deposition. We also investigated the modulation effect of midlife CA on the relationship between brain tau deposition and cognitive decline. Method One hundred four elderly subjects from the Korean Brain Aging Study for Early Diagnosis and Prediction of AD (KBASE) cohort underwent comprehensive clinical assessment and 18F‐AV‐1451 positron emission tomography (PET). Brain tau deposition in the inferior temporal (IFT) region on the PET imaging was assessed, and participating frequency of midlife CA was evaluated using a structured questionnaire (Wilson et al., 2005). Mini‐Mental State Examination (MMSE) score was used as a cognitive performance measure. Result Midlife CA did not show a significant association with IFT tau deposition (Figure 1). We found, however, a significant interaction effect between midlife CA and IFT tau deposition on MMSE score (Table). High midlife CA subgroup showed less steep decline of MMSE score with increase of tau than low CA subgroup (Figure 2). Conclusion The findings suggest that midlife CA can attenuate the harmful influence of brain tau deposition on late‐life cognition, while it does not directly change brain deposition of tau pathology.